Changes in Synaptic Properties in Cortical-Limbic Communications Induced by Repeated Treatments With Fluvoxamine in Rats - Satoshi Ohashi; Hiroko Togashi; Machiko Matsumoto; Kiyoshi Mori; Ken-ichi Ueno; Mitsuhiro Yoshioka (Elsevier, 2003)
There is evidence indicating that dysregulation of coordinated interactions of the cortical-limbic circuitry is associated with anxiety and mood disorders. Our previous study has reported that an enhancement of long-term plasticity in the "limbic-cortical" pathway produced by repeated treatments with fluvoxamine may be involved in the clinical effects of a selective serotonin (5-HT) reuptake inhibitor (SSRI). Here we assessed the effects of single and repeated treatments with fluvoxamine on the synaptic transmission and plasticity in the "cortical-limbic" pathway in vivo. The evoked potentials in the basolateral amygdaloid complex (BLA) by stimulation of the medial prefrontal cortex (mPFC) in halothane-anesthetized rats were recorded. Single administration of fluvoxamine (10 and 30 mg/kg, i.p.) enhanced the efficacy of synaptic transmission at the mPFC-BLA synapses dose-dependently. The enhanced synaptic efficacy induced by 30 mg/kg fluvoxamine was suppressed after long-term administration of fluvoxamine (30 mg/kg per day × 21 days, orally). Repeated treatments with fluvoxamine affected short-term, but not long-term, synaptic plasticity in the mPFC-BLA pathway. These findings indicate that the 5-HTergic system contributes to modulation of synaptic changes in this pathway. Our results also suggest that different changes in synaptic properties in cortical-limbic communications induced by repeated treatments with fluvoxamine may be associated with therapeutic effects of SSRI.